Toán Lớp 6: Tìm x: 1) (2x – 5) + 17 = 6 2) 10 – 2(4 – 3x) = -4 3) – 12 + 3(-x + 7) = -18 4) 24 : (3x – 2) = -3 5) -45 : 5(-3 – 2x) = 3 6) x.(x

Question

Toán Lớp 6: Tìm x:
1) (2x – 5) + 17 = 6
2) 10 – 2(4 – 3x) = -4
3) – 12 + 3(-x + 7) = -18
4) 24 : (3x – 2) = -3
5) -45 : 5(-3 – 2x) = 3
6) x.(x + 7) = 0
7) (x + 12).(x-3) = 0
8) (-x + 5).(3 – x ) = 0
9) x.(2 + x).( 7 – x) = 0
10) (x – 1).(x +2).(-x -3) =0, hướng dẫn giải giúp em bài này ạ, em cảm ơn thầy cô và các bạn nhiều.

in progress 0
Ngọc Sa 2 tháng 2022-12-19T04:35:04+00:00 1 Answer 0 views 0

TRẢ LỜI ( 1 )

  1. Giải đáp:
     
    Lời giải và giải thích chi tiết:
     1) (2x – 5) + 17 = 6
          2x – 5 + 17 = 6
          2x               = -6 => x=-3
    2) 10 – 2(4 – 3x) = -4
    10 -8 + 6x = -4
    6x = -6
    x = -1
    3) – 12 + 3(-x + 7) = -18
    – 12 -3x +21 = -18
    -3x = -27
    x = 9
    4) 24 : (3x – 2) = -3
    3x – 2 = -8
    3x = -6
    x = -2
    5) -45 : 5(-3 – 2x) = 3
    -15 -10x =-15
    -10x = 0
    x = 0
    6) x.(x + 7) = 0
    x = 0
    x + 7 = 0 => x= -7
    7) (x + 12).(x-3) = 0
    x + 12 = 0 => x = -12
    x-3 = 0 => x = 3
    8) (-x + 5).(3 – x ) = 0
    -x + 5 = 0 => x = 5
    3 – x = 0 => x = 3
    9) x.(2 + x).( 7 – x) = 0
     x = 0
    2 + x = o => x= -2
    7-x = 0 => x= 7
    10) (x – 1).(x +2).(-x -3) =0
    x – 1 = 0 => x = 1
    x +2 = 0 => x = -2
    -x -3 = 0 => x = – 3

Leave an answer

Browse

12:2+4x4-12:2-5x3 = ? ( )